Bird strike as a threat to aviation safety - Juračka, Jaroslav; Chlebek, Jiří; Hodaň, Viktor (Elsevier, 2021)
This article discusses air safety and the importance of safety studies as an effective tool for detecting safety risks. It has to provide a brief overview of Aviation Safety Hazards with a detailed look at the danger of collision of aircraft with birds. There is a technical description of course of events in the bird ingestion into the engine flying aircraft in the particular case. The final chapter generally deals with ways to minimize the risk.

This article discusses air safety and the importance of safety studies as an effective tool for detecting safety risks. It has to provide a brief overview of Aviation Safety Hazards with a detailed look at the danger of collision of aircraft with birds. There is a technical description of course of events in the bird ingestion into the engine flying aircraft in the particular case. The final chapter generally deals with ways to minimize the risk.
Bird strike as a threat to aviation safety
Keywords: Aviation Safety Hazard; Bird Strike; Engine; Damage; Aviation Safety Hazard; Bird Strike; Engine; Damage